Padrões biogeográficos e estruturação do conhecimento taxonômico das aranhas araneoideas americanas - Philip Russo da Silva (2019)
Biogeographic studies on a global scale are generally based on patterns of distribution and richness and there is not much understanding about variation in species composition. In these studies, the use of natural divisions as an alternative to the use of political boundaries is common, but as with political boundaries, the choice of natural divisions can also have some degree of arbitrariness. Alternatively, can be used areas on a global or macro scale that do not distinguish any divisions. In this work the American continent was used to evaluate the biogeographic patterns of spiders of the superfamily Araneoidea. Spiders are a significant portion of invertebrate diversity, and within the Araneae order, the Araneoidea superfamily stands out as the largest and best studied, and is a good model for the study of macro scale patterns. Despite this, the Wallacean shortfall is a reality for the group as well as for most organisms, especially invertebrates. In order to overcome this deficit, and to evaluate how our knowledge about the variation of the spider's distribution may be related to the sample effort over time, databases were constructed from the taxonomic literature available in the World Spider Catalog and the spatial distribution patterns and temporal analysis of these data through analyzes of richness, beta diversity and identification of areas of endemism. It was found that the spatial variation of the araneoidean spider richness in America is strongly related to the density pattern of records. For example, in the southern and southeastern regions of Brazil and southeastern United States, high species richness indexes and kernel density of occurrence records are associated with historically accumulated high collection effort. Something very similar happens with endemism patterns, the identification of these areas is also related to the density patterns of records, but despite this high correlation, and also having a strong historical influence, the identification of areas shows a great variation in their patterns as new distribution data is provided. This shows the importance of continuing to record the fauna and seek this information in places that are little known. Regarding species composition, this relationship with density and collection history is not well marked, and shows interesting results, with composition breaks very similar to some natural divisions proposed based on climatic variations, showing that this can be a factor that would be influencing spider distribution patterns in America.